Engaging non-governmental organizations in global climate governance: a systematic review of journal publications from 2014 to 2024 - Li, Zhidan; Yaakop, Mohd Rizal (Frontiers in Political Science, 2025)
Non-governmental organizations (NGOs) play a key role in climate governance, yet a systematic overview of their engagement at the global scale remains limited. This study aims to address this gap by systematically reviewing 40 empirical studies on NGO involvement in global climate governance. The principal findings of this research are that (1) most studies appeared in environment-focused and governance-related journals, covering less than a decade; (2) theoretical frameworks, predominantly materialist, underpinned most analyses; (3) qualitative methods, especially case studies, prevailed over quantitative approaches; (4) environmental and social NGOs were central actors, mainly engaged in policy option-identification and formulation; (5) both inside and outside strategies were widely used, while entrepreneurial strategies received less attention; and (6) organizational factors were more prevalent than state- or international-level dynamics in shaping NGO engagement. This study offers insights into how NGOs participate in global climate governance and suggests implications for future research, policymaking, and practice.